Heuristic discrepancy principle for variational regularization of inverse problems. (30th June 2020) - Liu, Huan; Real, Rommel; Lu, Xiliang; Jia, Xianzheng; Jin, Qinian
Abstract: We consider the variational regularization for inverse problems in a general form. Based on the discrepancy principle, we propose a heuristic parameter choice rule for choosing the regularization parameter which does not require the information on the noise level and is therefore purely data driven. Under variational source conditions, we obtain a posteriori error estimates. According to the Bakushinskii veto, convergence in the worst case scenario cannot be expected in general. However, by imposing certain conditions on the noisy data, we establish a convergence result for the heuristic rule. Applications of the results are addressed and numerical simulations are reported.